Evaluation of reproducible and transparent research practices in pulmonology - C.A. Smith; J. Nolan; D.J. Tritz; T.E. Heavener; J. Pelton; K. Cook; M. Vassar (Pulmonology)
Background Study reproducibility is valuable for validating or refuting results. Provision of reproducibility indicators, such as materials, protocols, and raw data in a study improve its potential for reproduction. Efforts to reproduce noteworthy studies in the biomedical sciences have resulted in an overwhelming majority of them being found to be unreplicable, causing concern for the integrity of research in other fields, including medical specialties. Here, we analyzed the reproducibility of studies in the field of pulmonology.Methods 500 pulmonology articles were randomly selected from an initial PubMed search for data extraction. Two authors scoured these articles for reproducibility indicators including materials, protocols, raw data, analysis scripts, inclusion in systematic reviews, and citations by replication studies as well as other factors of research transparency including open accessibility, funding source and competing interest disclosures, and study preregistration.Findings Few publications included statements regarding materials (10%), protocols (1%), data (15%), and analysis script (0%) availability. Less than 10% indicated preregistration. More than half of the publications analyzed failed to provide a funding statement. Conversely, 63% of the publications were open access and 73% included a conflict of interest statement.Interpretation Overall, our study indicates pulmonology research is currently lacking in efforts to increase replicability. Future studies should focus on providing sufficient information regarding materials, protocols, raw data, and analysis scripts, among other indicators, for the sake of clinical decisions that depend on replicable or refutable results from the primary literature.